Diagnostic Performance of Computed Tomography Scan with Core Biopsy in Assessing Paediatric Renal Tumour (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Although abdominal ultrasound is the first choice investigation to diagnose paediatric renal mass. But computed tomography (CT) can provide all informations regarding tumour staging, infiltration to surrounding structures and distant metastasis which is required for adequate diagnosis and treatment planning.Objective: To compare the accuracy of CT scan with core biopsy in assessing paediatric renal growth through analysis of accuracy, sensitivity, specificity, positive predictive value and negative predictive value comparing with histopathology as the gold standard.Methods: This cross sectonal study was conducted in Radiology and Imaging departments of CMH Dhaka and Dhaka Medical college and hospital, Department of pathology,Dhaka Medical college hospital and Armed forces institute of pathology and from July 2021 to June 2022 . A total of 50 pediatric patients were selected who came for CT scan with clinical suspicion of renal growth after taking informed consent. CT Image findings and core biopsy reports of paediatric renal masses were compared and correlated. Results: Male female ratio was 1.17:1 with age ranging from birth to 12 years and most of the patients were between 2-3 years. In CT Wilms tumour was found in 43 patients, Mesoblastic nephroma in 02, renal cell carcinoma in 01, Multilocular cystic nephroma in 04 patients. Forty four were diagnosed as malignant by CT and among them 43 were confirmed by core biopsy. Again 07 cases are diagnosed as benign by CT and among them only 1 case was malignant in core biopsy. So, among 50 cases total 44 were confirmedmalignant histopathologically. Sensitivity, accuracy and specificity of CT in diagnosis of only Wilms tumours were 97.7%, 96% and 85.7%respectively. Chi-square test showed a p-value of >0.05 which established no statistical significant difference between CT and core biopsy. In overall CT diagnosis of paediatric renal growth, similarity was found in both sensitivity and positive predictive value (97.7%) but accuracy was different (96.0%) where similarity also found between specificity and negative predictive value (83.3%). Conclusion: CT is a noninvasive, ideal and reliable imaging modality for evaluating paediatric renal mass in comparison to core biopsy.